Portrayal of Weaker Sections in Secondary Level School Textbook of English: A Study - JAISI, UZMA HUSAIN; LODI, ADNAN KHAN (JOURNAL OF INDIAN EDUCATION, 2025)
Textbooks can have a significant impact on how a certain social groups is portrayed through both literary and visuals means. To help students comprehend the needs and reality of every people, public institutions must provide a realistic and non-judgemental image of all in their curriculum. The current study set out to locate and evaluate, how the English textbook which is utilised for the CBSE Board, portrays the weaker sections of the Indian society. Using coding–based categories, a content analysis of the text and visuals from a sample textbook was carried out. The three main categories that steer the analysis are—socially disadvantaged populations, people with disabilities and gender identities. When we looked at the textbook, we saw that majority of the chapters were focused on men as compare to females and features just one disabled character in the textbook. The textbook comprises a chapters on poverty like chapter of 5 ‘The Snake and the Mirror’ by V. M. Basheer (Bechive, 2006 pg 56) where the narrator is a poor homeopath doctor with little money that comes under socially disadvantaged populations. Suggestions were also mentioned in the study for improvement of the textbooks.